Hepatitis C Virus NS2 Protein Inhibits DNA Damage Pathway by Sequestering p53 to the Cytoplasm - Bittar, Cintia [UNESP]; Shrivastava, Shubham; Bhanja Chowdhury, Joydip; Rahal, Paula [UNESP]; Ray, Ratna B. (Public Library of Science (PLoS), 2013)
Chronic hepatitis C virus (HCV) infection is an important cause of morbidity and mortality globally, and often leads to end-stage liver disease. The DNA damage checkpoint pathway induces cell cycle arrest for repairing DNA in response to DNA damage. HCV infection has been involved in this pathway. In this study, we assess the effects of HCV NS2 on DNA damage checkpoint pathway. We have observed that HCV NS2 induces ataxia-telangiectasia mutated checkpoint pathway by inducing Chk2, however, fails to activate the subsequent downstream pathway. Further study suggested that p53 is retained in the cytoplasm of HCV NS2 expressing cells, and p21 expression is not enhanced. We further observed that HCV NS2 expressing cells induce cyclin E expression and promote cell growth. Together these results suggested that HCV NS2 inhibits DNA damage response by altering the localization of p53, and may play a role in the pathogenesis of HCV infection. © 2013 Bitter et al.
Keywords: checkpoint kinase 2; cyclin E; nonstructural protein 2; protein p21; protein p53; cell growth; cell proliferation; controlled study; cytoplasm; DNA damage; Hepatitis C virus; nonhuman; protein expression; protein function; protein localization; protein transport